The Positive Impact of Problem Based Learning Model toward Students’ Science Knowledge Competence - Dwi Marta Anggreni; I Gusti Agung Oka Negara (Jurnal Ilmiah Sekolah Dasar, 2020)
This study was conducted with the aim of finding out the significant differences between the science knowledge competencies of the group of students who were taught using the project based learning model and the groups of students who were taught conventionally in the fifth grade. This research is a quasi-experimental research design using nonequivalent control group design. The population of this study, are consisted of 7 classes consisting of 183 students. The sampling technique used in this study was quota sampling by determining from the beginning the sample to be used according to the desired quota, then drawing to determine the experimental class and the control class so that the fifth grade SD No. 2 Blahkiuh with 40 students as a group of experimental class and fifth grade of elementary school No. 2 Sangeh with 44 students as the control class group. The usual 36 multiple choice objective tests that have been validated are used to obtain student science competency data. Grade V grade average SD No. 2 Blahkiuh as an experimental class that is 84.98 included in the high criteria, greater than the average grade V SD No. 2 Sangeh as a control class that is 79.77 including high criteria. The results of the t-test analysis showed tcount> ttable ie 2, 591> 2,000 at the 5% significance level and dk = 84, so that the observation hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted stating there were significant differences. Thus, it can be concluded that the Project Based Learning Model has an effect on the science competency of the fifth grade